Older Workers and Working Time - David N. F. Bell; Alasdair C. Rutherford (Institute for the Study of Labor (IZA), 2013)
Contrary to much of the established literature, this paper finds that though many older workers would prefer to reduce their working hours (the overemployed), there is a significant group who would like to work longer hours (the underemployed). And contrary to the assumption that the self-employed are more easily able than employees to select a desired combination of hours and the wage rate, this paper finds that older self-employed workers are more likely to wish to adjust their hours, both upward and downward than are employees. A new index of underemployment is used to show that for the UK, since the onset of the Great Recession, underemployment among older workers has been growing more rapidly than unemployment. Using longitudinal data from the UK Labour Force Survey, the paper investigates the effects of overemployment and underemployment on transitions from employment and self-employment into other labour market states. It confirms that overemployment is a significant predictor of retirement among employees while underemployed employees are less likely to retire.
Keywords: J01; J11; J21; J22; J23; J38; J64; 330; retirement; working time; overemployment; underemployment; self-employment